The role of the TIM-3 receptor in inflammatory bowel disease and autoimmunity: implications for TIM-3 and TCR crosstalk - Gabel, Michael; Knauß, Annkathrin; Neurath, Markus; Weigmann, Benno (Journal of Molecular Medicine, 2026)
The T cell immunoglobulin and mucin-domain receptor 3 (TIM-3) is an immune checkpoint receptor with complex effects on T cell activation and tolerance. TIM-3 is expressed on the surface of T cells in close proximity to the T cell receptor (TCR), where it mainly acts co-inhibitory, despite lacking typical inhibitory immunoreceptor inhibition motifs, to regulate T cell activity or apoptosis. However, the underlying molecular mechanisms of its intracellular signal transduction remains incompletely understood. Central for the function of TIM-3 are conserved cytoplasmic tyrosine structures that require phosphorylation for downstream signaling. Previous findings suggest that several kinases linked to TCR signaling, including the Src family kinase Lck and the Tec kinase ITK can interact with TIM-3 and thereby regulate TCR signaling and fine-tune T cell activation and tolerance. The ligand-dependent phosphorylation of TIM-3 by ITK, together with the displacement of the adapter protein Bat3, illustrates how TIM-3 signaling modulates early TCR activation. In this review, we describe the interactions of TIM-3 and its various actors that can trigger TCR signaling. This review also aims to shed light on this complex network by providing an overview of the immune checkpoint receptor TIM-3 and its influence on various autoimmune diseases. The focus here is clearly on inflammatory bowel disease (IBD), and open questions about the TIM-3 network are outlined.
CRIS-Team Scopus Importer:2026-01-09
Keywords: Autoimmune disease; Inflammation; Inflammatory bowel disease; T cell receptor; TCR-signaling; TIM-3